Fitonematoides associados a nogueira-pecã no Rio Grande do Sul e correlação com os atributos do solo - Romagna, Izabelle Scheffer (2022)
Rio Grande do Sul is the largest pecan producer in the country. This crop is gaining space on small and medium farms because of its profitability, longevity, and possibility of income diversification. Because it is a relatively new crop in the country, studies related to nematodes are scarce, although much discussed and studied in other producing countries. Thus, the present study aimed (1) to characterize phytoparasite genera present in soils cultivated with pecan walnut, in different producing regions in the state of Rio Grande do Sul, and (2) to evaluate the susceptibility of pecan walnut, cultivar Barton, to the phytonematode Mesocriconema xenoplax (Raski, 1952). For study I, a survey of phytonematode genera present in soils and roots of pecan nuts from twelve orchards, located in eight municipalities of the state (Cachoeira do Sul, Santa Maria, Bento Gonçalves, Catuípe, Ijuí, Anta Gorda, Pantano Grande and Encruzilhada do Sul) was carried out. After collection, the samples were submitted to nematode analysis and soil analysis. The genera belonging to the family Criconematidae were identified to species level by morphological and morphometric analysis. From the nematode analysis eight phytoparasitic genera were found (Mesocriconema, Criconemoides, Discocriconemella, Xiphinema, Tylenchus, Pratylenchus, Helicotylenchus and Aphelenchoides), whereby Mesocriconema and Helicotylenchus were the most frequent and abundant. The species M. xenoplax, Mesocriconema ornatum, Criconemoides ixhaphozi and Discocriconemella degrissei were identified. The population densities of Mesocriconema and Criconemoides showed a strong correlation, showing that as certain conditions favor an increase in the density of one genus, so does the other. No population suppression of one population was observed at the expense of the other. In addition, Mesocriconema showed a negative correlation with most soil attributes, suggesting that these attributes do not interfere with its population frequency. Due to the higher frequency of the genus Mesocriconema in the analyzed orchards, study II was developed, where pecan walnut seedlings, cultivar Barton, were inoculated with M. xenoplax. The following were evaluated: plant height (cm), main root length (cm), root system fresh mass (g), stem diameter (mm), number of nematodes in the soil and roots of inoculated plants and the reproduction factor. Pecan walnut seedlings, cultivar Barton, were susceptible to the nematode M. xenoplax under greenhouse conditions after 180 days of inoculation. The presence of this nematode resulted in reduced height, stem diameter, fresh mass and length of the root system of the plants, as well as marked symptoms of wilting, chlorosis and necrosis in the seedlings. In view of these results, we suggest the development of further research on the susceptibility of pecan cultivars used in the state, as well as the genetic characterization of genera associated with the culture.